Современные механизмы развития профессиональных компетенций педагога в электронной образовательной среде (SCIENCE and SOCIETY, 2023)
The article reveals the features of the continuous development of professional competence in the profes- sional training of teachers using innovative pedagogical and production technologies. It is proposed to use pedagogical technologies of distance and project-based learning, as well as advanced production technologies for the formation of pro- fessional competencies among participants in the educational process (teachers and students). The educational and method-